2021
DOI: 10.1017/aer.2021.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forebody boundary layer on the performance of a submerged inlet

Abstract: The use of a submerged inlet is advantageous in modern aircrafts because of its low drag resistance, small radar cross section and ease of maintenance. Although it is well known that the forebody boundary layer deteriorates the aerodynamic performance of a submerged inlet, the level of impact has not yet been fully quantified. To quantify the forebody boundary-layer effect, a submerged diverter was designed to remove a portion of the low-energy boundary flow. The flow pattern and aerodynamic performance of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Rein and Koch 48 demonstrated that the distortion at the AIP increases proportionally with the thickness of the inlet boundary layer. Thick boundary layers were found to reduce also the pressure recovery on the intake 49 51 and to promote non-uniform radial pressure loading on the compressor blades which could trigger stall inception. 4 Different azimuthal orientations of the approaching boundary layer were also investigated for intakes under yaw and pitch angles 52 , 53 , 18 were found to notably influence the fan-face pressure and swirl distortion.…”
Section: Introductionmentioning
confidence: 99%
“…Rein and Koch 48 demonstrated that the distortion at the AIP increases proportionally with the thickness of the inlet boundary layer. Thick boundary layers were found to reduce also the pressure recovery on the intake 49 51 and to promote non-uniform radial pressure loading on the compressor blades which could trigger stall inception. 4 Different azimuthal orientations of the approaching boundary layer were also investigated for intakes under yaw and pitch angles 52 , 53 , 18 were found to notably influence the fan-face pressure and swirl distortion.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, how to improve aerodynamic performance of submerged inlets has become a key issue. Many scholars have conducted series of research on it, including the optimization of the design of the inlet shape [5][6][7][8][9], the application of active flow control methods such as jet [10][11][12][13][14][15][16], and the exploration of passive flow control methods such as setting synergistic components near the inlet [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the ridge structure can split the boundary layer before the inlet's entrance, but it is necessary to ensure that the swirling vortex of the side edge of the inlet can pass through safely. Xie et al [25] proposed a method to remove part of the low-energy boundary flow and improve the inlet's performance by setting a submerged deflector in front of submerged inlet and studied it through numerical simulation and wind tunnel tests. After adding the submerged deflector, the inlet's total pressure recovery coefficient is increased by 3.3%, and its circumferential distortion DC60 is reduced by 28.2%.…”
Section: Introductionmentioning
confidence: 99%
“…Xie designed a boundary layer splitter that improved the quality of airflow inside the intake duct by displacing the lowenergy flow in the boundary layer. The study results showed an improvement of 3.3% in the total pressure recovery coefficient of the intake duct and a 28.2% reduction in circumferential distortion DC60 [21]. Saheby designed a ridge-type vortex generator near the entrance, which can divert the boundary layer at the intake entrance.…”
Section: Introductionmentioning
confidence: 99%